2022
DOI: 10.3847/1538-4357/ac67a6
|View full text |Cite
|
Sign up to set email alerts
|

Local Spiral Structure Traced by Red Clump Stars

Abstract: Using the cross-matched data of Gaia EDR3 and the Two Micron All Sky Survey Point Source Catalog, a sample of RC stars with parallax accuracies better than 20% is identified and used to reveal the nearby spiral pattern traced by old stars. As shown in the overdensity distribution of RC stars, there is an arc-like feature extending from l ∼ 90° to ∼243°, which passes close to the Sun. This feature is probably an arm segment traced by old stars, indicating the galaxy potential in the vicinity of the Sun. With a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…We find a correspondence between the overdensities in this sample and these reported by Poggio et al (2021) for the younger UMS population (fourth panel); although some discrepancies are observed at (X, Y) ≈ (−1, −9) kpc and (−2,−6.5) kpc. The presence of the spiral arms traced by an old population has been recently proposed by Lin et al (2022), who identified the Local Arm in a sample of 87 000 Gaia EDR3-2MASS (Gaia Collaboration 2021; Skrutskie et al 2006), Red Clump stars (RC) and could be related to the metallicity asymmetry in Sample B and C in Poggio et al (2022, see their Fig. 1).…”
Section: Spiral Armsmentioning
confidence: 64%
See 1 more Smart Citation
“…We find a correspondence between the overdensities in this sample and these reported by Poggio et al (2021) for the younger UMS population (fourth panel); although some discrepancies are observed at (X, Y) ≈ (−1, −9) kpc and (−2,−6.5) kpc. The presence of the spiral arms traced by an old population has been recently proposed by Lin et al (2022), who identified the Local Arm in a sample of 87 000 Gaia EDR3-2MASS (Gaia Collaboration 2021; Skrutskie et al 2006), Red Clump stars (RC) and could be related to the metallicity asymmetry in Sample B and C in Poggio et al (2022, see their Fig. 1).…”
Section: Spiral Armsmentioning
confidence: 64%
“…The J R maps suggest a connection between the Perseus and the Local Arm (Structures C and B, respectively). However, the spatial geometry of the spiral arms from UMS stars (Poggio et al 2021), Red Clump stars (Lin et al 2022), and the giant sample does not coincide with the observed features in J R in this region.…”
Section: Spiral Armsmentioning
confidence: 74%
“…For instance, the structures traced by young OB stars are consistent with those traced by masers associated with HMSFRs (e.g., Xu et al 2018aXu et al , 2018bXu et al , 2021b. Additionally, the large age spans of open clusters made them suitable for studying the motion and evolution of spiral arms (e.g., Hao et al 2021), and even main-sequence stars and old stars can be used to constrain spiral arm structure (e.g., Poggio et al 2021;Lin et al 2022).…”
Section: Introductionmentioning
confidence: 66%
“…By comparing the spiral arm structures traced by masers with those traced by OB stars and open clusters obtained from Gaia astrometry, it is possible to study the consistency of the spiral arm structures traced by different young objects and the homogeneity of the distribution of star formation in the spiral arms (e.g., Xu et al 2018aXu et al , 2021b. Naturally, we also expect SKA-VLBI to be able to observe the spiral arm structure depicted by other tracers, such as AGB stars (see Section 3.1.2), which can be compared with the results from Gaia astrometry to study the spiral arm structure traced by old objects (e.g., Poggio et al 2021;Lin et al 2022). It is also interesting to compare the spiral structure traced by old and young objects (e.g., Lin et al 2022).…”
Section: The Structure Of the Milky Waymentioning
confidence: 87%
See 1 more Smart Citation